Improving Students’ English-Speaking Skills Through Project Video: English - Euis Meinawati; Rahaida Rahayu; Widia Yunita; Chodidjah Chodidjah; Elpa Hermawan (Prodi Tadris Bahasa Inggris, 2024)
The purpose of this study is to examine the effectiveness of implementing English-speaking learning through video projects. This study employed a quasi-experimental approach, with one group undergoing pre-test and post-test experiments. The study was done in 12 meetings with 36 English-speaking students from class X IPA during the third odd semester of the academic year 2023-2024. The study will run from August 2023 until November 2023 at SMAN 14 Depok. Data were acquired by observation, documentation, and a speaking exam. The data was analyzed using a two-sample paired t-test for the mean. The study found that individual video projects can improve students' engagement in speaking sessions. In addition, pupils find it easier to generate speaking ideas. As a result, pupils' English writing skills improved more than before the video project work was established. The t-test results indicate that individual video projects can increase English speaking skills, as t-Stat < t-table (10.62922427 < 2.030107928).